Operational group for process safety. Issue 1 (27th November 2012) - Saraiva, Maria Clara Barros e Silva; Abreu, Rosemeire
<x xml:space="preserve">Abstract</x> In order to create a process safety culture, the engineers at Braskem's Utility Unit decided to organize a group that comprised operators and engineers to develop a preventive strategy for accidents and mishaps. This work was developed in a utility center integrated to Braskem Basic Petrochemical 1 Site in Brazil. The center produces clarified water, demineralized water, steam in different levels of pressure, compressed air, and electric energy to a petrochemical complex, including a 1, 250, 000 ton per year olefins site. As the process evolved, a large range of knowledge among engineers and operators was found. © 2012 American Institute of Chemical Engineers Process Saf Prog 32: 22–24, 2013